Recontextualizing Swedish nationalism for commercial purposes: a multimodal analysis of a milk marketing event. Issue 5 (20th October 2019) - Andersson, Helen
ABSTRACT: In this paper, I carry out an analysis of an event in Sweden called 'the spring turnout'. It is a traditional event where cows are allowed out into the fields after the winter. I show how it has been colonized by Arla Foods, the diary company which controls part of the milk production in Sweden and in many other countries. Of interest in this analysis is how Arla infuses the event, and its own marketing, with discourses about nature that are specifically Swedish and can be traced to the nation building of the nineteenth and twentieth centuries, used systematically as part of the social democratic project for equality and progress through a strong welfare system. The paper examines how Arla recontextualizes these discourses for commercial purposes. I show how such recontextualized discourses carry reassurances to Swedish people that this project is still intact despite huge social political changes in Swede over the past decades embracing neoliberalism, global capitalism and becoming one of the fastest deregulating countries in the world.